Multi-detector thermal field-flow fractionation (ThFFF) as a characterization technique for complex polymer self-assemblies - Muza, Upenyu Lucky (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2017.